(untitled) (CIPEEX, 2025)
RISKS AND BENEFITS OF BLEPHAROPLASTY: AN ANALYSIS OF THE MAIN COMPLICATIONSCamila Santa Bárbara Bernardino¹, Haroldo Neto Diniz Antônio¹, Humberto Renato de Oliveira Filho¹, Maria Fernanda Dias de Paula¹, Luis Ricardo Lara Pereira¹, Victor Almeida Chaves¹, Claudinei Sousa Lima²¹Medical students at the Evangelical University of Goiás - UniEVANGÉLICA²Professor at the Evangelical University of Goiás - UniEVANGÉLICAIntroduction:Several factors influence human aging, such as gravity, repetitive actions of certain muscles, and time itself. The first signs of aging often appear in the eye area. In this context, blepharoplasty is one of the most commonly performed plastic surgeries, aiming to reshape structures and restore a youthful appearance to the patient. It is therefore crucial to highlight the main complications that can arise from this type of procedure.Objectives:The objective of this study is to highlight the risks and benefits surrounding blepharoplasty surgery by analyzing its main complications.Methodology:This is an integrative review with studies retrieved from the LILACS and SciELO databases, using the descriptors (DeCS): “blepharoplasty,” “intraoperative complications,” and “risk measurement,” along with the boolean operators “AND” and “OR.” A total of 95 articles were found, of which four were included in the study. Articles that were only tangentially related to the topic, published more than ten years ago, or not written in Portuguese were excluded.Results and Discussion:In most cases, complications in blepharoplasty surgery are infrequent and, when they occur, are minor and transient. Chemosis was found to be the most common complication. Ectropion, a significant complication that occurs when there is excessive resection of skin or muscle from the lower eyelid, retracting it, can also occur. Adequate preoperative care and some preventive measures can avoid this complication. Other possible complications include temporary detachment of the lateral portion of the lower eyelid, bilateral paresthesia of the frontal and parietal regions of the scalp, hemorrhage, exposure keratopathy, lacrimal gland resection, excessive fat removal, ptosis, and upper eyelid retraction. Ptosis may occur secondary to edema, hematoma, or anesthetic toxicity.Final Considerations:Blepharoplasty can be extremely beneficial for a patient’s self-esteem, especially when performed correctly and with appropriate precautions. Complications are rare, and when they do occur, the most common can be resolved with simple measures, while more severe ones are rarely observed. Therefore, in a well-executed procedure by a qualified professional, the benefits to the patient’s self-image largely outweigh the risks of the surgery.Keywords: blepharoplasty, intraoperative complications, risk measurement